Rural Finance Policies 5 - Current state of development and prospects for microfinance institutions - Lapenu, Cecile (International Food Policy Research Institute, 2000)
The database compiled by IFPRI (see policy brief on microfinance institutions [MFIs] in Africa, Asia, and Latin America) counts almost 1,500 microfinance institutions (688 in Indonesia and 790 in other countries) supported by international organizations in 85 developing countries. They reach 54 million members: 44 million of them save, and 23 million of them borrow. The total volume of outstanding credit stands at $18 billion and the total savings volume stands at $13 billion, or 72 percent of the volume of the outstanding loans. MFIs operated out of at least 46,000 branches and employed around 175,000 persons. Analyzing this world of mushrooming MFIs can provide fresh insights on potential service outreach and the overall role of MFIs in developing countries.